Monitoring leaning towers by geodetic approaches: effects of subsidence and earthquake to the Ghirlandina Tower. Issue 3 (10th September 2015) - Castagnetti, Cristina; Bertacchini, Eleonora; Capra, Alessandro
Summary: The research focuses on structural monitoring and movements identification applied to cultural heritage protection. The final purpose is the integration among different and independent technologies for analyzing and investigating the geometry changing over time of ancient leaning towers. The paper deals with a novel strategy implemented to compute differential vertical displacements starting from results obtained by repeated high‐precision leveling network adjustments. These results usually aim at monitoring the subsidence phenomenon, while their use in engineering applications is more or less absent in literature. Moreover, the multidisciplinary approach is also able to analyze subsidence gradients in order to extrapolate the trend of the vertical axis and compute structure's rotations. The approach is applied to the Ghirlandina Tower, Modena (Italy), in order to identify the leaning and the subsidence trend. About 30 years of leveling campaigns provide a useful dataset to test the methodology, which is finally validated by the independent observations collected by a pendulum. The approach allows to compute the mean total displacement since 1984 of about 4.7 cm with 30% occurring over the last 6 years. In the same period, the total overhang of the tower (1.30 m in 2007) increased by about 19.1 and 10.4 mm towards southwest. The approach is also able to identify anomalous behavior of the tower such as the reversal tilting trend due to the scaffolding in the years of restoration and the permanent deformation suffered after the 2012 Emilia Romagna earthquake (failure of 4 mm in 6 months). Copyright © 2015 John Wiley & Sons, Ltd.